Targeting Hispanic Immigrants with Food Safety Communications - Kristina M. Boone; Karen Penner; Becky Johnson; Audrey Young; Charles Lubbers (Journal of Applied Communications, 2004)
Hispanics are the largest minority population in the United States, according to the 2000 U.S. Census, and the fastest growing. If they are immigrants, they are often dealing with cultural issues as well as new technological applications and social systems. The need for education programs and dissemination of food safety information to this growing segment of the population is evident. This study sought to determine the group’s knowledge of food safety and its primary channels for receiving such information. A questionnaire was developed and translated into Spanish. Face-to-face data collection facilitated by a trusted community partner proved to be a successful means of collecting data from this audience, who are often difficult to reach and may be unwilling to speak with people associated with government. Specific areas of lack of knowledge emerged. The respondents struggled most with questions about proper handling of leftovers containing meat, accurate water temperature for washing and rinsing dishes, handling frozen foods, and defrosting meat. From the attitude questions, the authors found that the target group felt food safety was important, was more threatened in food service outlets than in the home, and was overemphasized. The channel used most frequently and trusted most was television.